Pushing the boundaries : Virgilia oroboides (Keurboom) facilitated expansion of forest in to fynbos - Nortje, G (Department of Biological Sciences, 2015)
The boundary between forest and fynbos vegetation in the Southern Cape of South Africa present a dynamic ecotone in which forest has previously been noted to have expanded into fynbos territory. Forest colonization of fynbos has been shown to be primarily a function of nutrients and light environments in the understory which may or may not be conducive for the growth of forest species. Additionally, it is understood that fire regime is the primary agent in determining forest/fynbos boundaries. Virgilia oroboides is a fast-growing leguminous tree confined to the margin between forest and fynbos. It has long been thought to facilitate the growth of forest species through the heavy shading and nutrient enrichment of soils; both of which facilitate the growth of forest seedlings. Furthermore, V. oroboides is predicted to reduce fuel loads and as a result prevent fire penetration of forests. These possible functions were tested by sampling soils, nutrient content of leaves and the shade cast by plants 18 months after a burn on a forest margin near Swellendam, Southern Cape. In addition, the effects of varying density of Virgilia on surrogates for fuel biomass, and forest seedling growth, were observed at Silvermine on the Cape Peninsula. Shaded environments produced by V. oroboides are shown to have detrimental effects on the growth of fynbos, while facilitating the growth of forests. V. oroboides had the highest soil nutrient enrichment potential of all species investigated and is therefore predicted to produce nutrient cycling processes conducive to the growth and regeneration of forests. Estimates of fuel in the understory of V. oroboides are predicted to reduce fynbos fire severity upon reaching the margin. These results suggest that Virgilia does indeed facilitate forest tree species more than light-demanding fynbos species so that its presence should result in greater stability or slow expansion of forests into fynbos. If supported by further work, this facilitative role of Virgilia has management implications for the conservation of fynbos and forests in the Southern Cape of South Africa.